VD_FINDINFO Jug / 2020 / 181 vom 13. September 2019 - VD Tribunal cantonal (2019)
LÉSION CORPORELLE SIMPLE, VIOLENCE CONTRE LES AUTORITÉS | 106 al. 2 CP, 123 ch. 1 CP, 285 ch. 1 CP, 42 al. 1 CP, 42 al. 4 CP